Management of Oligospermia (Ksheena Shukra) through Ayurveda: A Case Study - Upadhyay, Rohit; Vasan, Satish S (International Research Journal of Ayurveda & Yoga, 2022)
As per today’s lifestyle, stress and sedentary work habits are being the biggest cause for infertility. The objective of the case study is to use Panchkarma procedure to increase the sperm count for a healthy progeny. A 29 year old married man visited the OPD of department of Panchakarma of Sidramppa Danigond Memorial Trust”s Ayurvedic Medical College Terdal on 19-09-2020. He had complained of decreased sexual interest and generalized weakness also. It is pathological condition of Shukra in which there may be reduced sperm count. In classics many Shukra Janaka drugs are explained in Ksheena Shukra condition. The patient was treated using Basti Karma and supportive Ayurvedic therapy for Ksheena Shukra. This case was managed with Anuvasan basti for 10 days and then the patient was administered Shaman Chikitsa for 30 days. The detail of this case highlights the role of Shodhana and Shamana Chikitsa in the management of Oligospermia.